Financial interdependence or contagion? evidence from a meta-analysis - Zhang, H. C.; Mohamad, Azhar; Hamid, Zarinah (Statistical Economic and Social Research and Training Centre for Islamic Countries, 2019)
During the last two decades, the phenomenon of financial contagion has been investigated in numerous pieces of research. In spite of its severe implications for the stability of domestic financial systems as well as potential diversification benefits of international portfolio investment, there has yet to be universally agreed conclusion on the relevance of financial contagion. Thus, our current study has been designed to apply the meta-analysis approach to investigate the statistical significance of financial contagion based on past empirical contagion studies. Our meta-analysis concludes that financial contagion is a significant phenomenon. As implications, policy makers should establish contingent credit lines to ensure the liquidity of financial market during the turbulence time, and portfolio investors should diversify away from the potentially contagious markets. It is suggested that future contagion-based meta-analysis may include contagion studies with different methodologies, as well as meta-regression analysis to provide more insights on the sources of variability in the contagion studies.